Xylazine co-occurrence with illicit fentanyl is a growing threat in the Deep South: a retrospective study of decedent data - William Bradford; Mary Figgatt; Karen S. Scott; Stacy Marshall; Ellen F. Eaton; Daniel W. Dye (BMC, 2024)
Abstract Background Xylazine is a dangerous veterinary sedative found mainly in illicit fentanyl in the Northeast and Midwest. Its role in the Deep South overdose crisis is not well-characterized. Methods We conducted a retrospective review of autopsy data in Jefferson County, Alabama to identify trends in xylazine prevalence among people who fatally overdosed from June 2019 through June 2023. Results 165 decedents met inclusion criteria. While the first identified xylazine-associated overdose was in June 2019, xylazine has become consistently prevalent since January 2021. All cases of xylazine-associated fatal overdoses were accompanied by fentanyl, and most (75.4%) involved poly-drug stimulant use. The average age was 42.2, and most decedents were white (58.8%) and male (68.5%). Overall, 18.2% of people were unhoused at the time of death. Discussion Xylazine is prevalent in the Deep South. Efforts to promote harm reduction, publicly viewable drug supply trends, and legalization of drug checking and syringe service programs should be prioritized.